Trends in the Use of Professional Facebook in Ranggo Village Analysis: Gender Studies in the Perspective of Islamic Education - Yeni, Yeni; Irwan Supriadin; Indriani, Irma (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The development of digital technology has affected the social, economic, and educational interaction patterns of the community, including in rural areas. This study aims to analyze the trend of using Professional Facebook (FB-Pro) in Ranggo Village by reviewing differences based on gender and its relevance in the perspective of Islamic Education. The research used a descriptive qualitative method with interview, observation, and documentation techniques on 10 content creators (5 men and 5 women) and 2 religious figures. The data is analyzed with a thematic approach to identify key patterns, themes, and categories. The results of the study show that FB-Pro is used by the public not only as a means of entertainment, but also as an economic opportunity through content monetization. The gender difference is quite significant: men tend to be limited to personal content and hobbies, while women are more creative, expressive, and successfully use FB-Pro for economic purposes. In terms of Islamic education, religious leaders emphasized that social media should be directed to useful activities, such as da'wah, education, and the dissemination of positive information. This study concludes that FB-Pro has great potential as a medium for da'wah, learning, and community empowerment, although it is currently more predominantly used for entertainment. Therefore, digital education based on Islamic values that emphasizes ethics, responsibility, and gender equality is needed so that the use of social media can provide benefits for the people.